Determining Instantaneous Centers of Rotation for Finger Joints Through Different Postures Using the Iterative Closest Point Algorithm (ICP). (September 2016) - Figueroa, Rosemarie; Armstrong, Thomas J.; Woolley, Charles; Sun, Luqin; Zhou, Wenxuan; Sebastin, Sandeep
Hands are primary means by which we perform activities of daily living, work, and leisure. This work is concerned with development of a kinematic model for predicting hand posture and product and manual work design. Anatomical parameters of the hand bones were obtained by medical imaging, to determine instantaneous centers of rotation of finger joints. Posture data is captured from different grasping postures of the same hand. This work focuses specifically on the joints of the phalange 3.